Effects of exercise on leukocyte death: prevention by hydrolyzed whey protein enriched with glutamine dipeptide - Cury-Boaventura, M. F.; Levada-Pires, A. C.; Folador, A.; Gorjao, R.; Alba-Loureiro, T. C. (European Journal of Applied Physiology, 2008)
Lymphocyte and neutrophil death induced by exercise and the role of hydrolyzed whey protein enriched with glutamine dipeptide (Gln) supplementation was investigated. Nine triathletes performed two exhaustive exercise trials with a 1-week interval in a randomized, double blind, crossover protocol. Thirty minutes before treadmill exhaustive exercise at variable speeds in an inclination of 1% the subjects ingested 50 g of maltodextrin (placebo) or 50 g of maltodextrin plus 4 tablets of 700 mg of hydrolyzed whey protein enriched with 175 mg of glutamine dipeptide dissolved in 250 mL water. Cell viability, DNA fragmentation, mitochondrial transmembrane potential and production of reactive oxygen species (ROS) were determined in lymphocytes and neutrophils. Exhaustive exercise decreased viable lymphocytes but had no effect on neutrophils. A 2.2-fold increase in the proportion of lymphocytes and neutrophils with depolarized mitochondria was observed after exhaustive exercise. Supplementation of maltodextrin plus Gln (MGln) prevented the loss of lymphocyte membrane integrity and the mitochondrial membrane depolarization induced by exercise. Exercise caused an increase in ROS production by neutrophils, whereas supplementation of MGln had no additional effect. MGln supplementation partially prevented lymphocyte apoptosis induced by exhaustive exercise possibly by a protective effect on mitochondrial function.